Specific aneusomies in Chinese hamster cells at different stages of neoplastic transformation, initiated by nitrosomethylurea - Fabarius, Alice; Willer, Andreas; Yerganian, George; Hehlmann, Rüdiger; Duesberg, Peter (Proceedings of the National Academy of Sciences of the United States of America, 2002)
Aneuploidy is ubiquitous in cancer, and its phenotypes are inevitably dominant and abnormal. In view of these facts we recently proposed that aneuploidy is sufficient for carcinogenesis generating cancer-specific aneusomies via a chain reaction of autocatalytic aneuploidizations. According to this hypothesis a carcinogen initiates carcinogenesis via a random aneuploidy. Aneuploidy then generates transformation stage-specific aneusomies and further random aneusomies autocatalytically, because it renders chromosome segregation and repair mechanisms error-prone. The hypothesis predicts that several specific aneusomies can cause the same cancers, because several chromosomes also cooperate in normal differentiation. Here we describe experiments on the Chinese hamster (CH) that confirm this hypothesis. (i) Random aneuploidy was detected before transformation in up to 90% of CH embryo cells treated with the carcinogen nitrosomethylurea (NMU). (ii) Several specific aneusomies were found in 70–100% of the aneuploid cells from colonies transformed with NMU in vitro and from tumors generated by NMU-transformed cells in syngeneic animals. Among the aneuploid in vitro transformed cells, 79% were trisomic for chromosome 3, and 59% were monosomic for chromosome 10, compared with 8% expected for random distribution of any aneusomy among the 12 CH chromosomes. Moreover, 52% shared both trisomy 3 and monosomy 10 compared with 0.6% expected for random distribution of any two aneusomies. Among the tumor cells, 65% were trisomic for chromosome 3, 51% were trisomic for chromosome 5, and 30% shared both trisomies. Aneuploid cells without these specific aneusomies may contain minor transformation-specific aneusomies or may be untransformed. (iii) Random aneusomies and structurally altered chromosomes increased with the generations of transformed cells to the point where their origins became unidentifiable in tumors. We conclude that specific aneusomies are necessary for carcinogenesis.
Gesehen am 17.05.2022